Analisis Ijaz Dalam Ilmu Balaghah Pada Al-Baqarah Ayat: 285: Kewajiban Beriman Kepada Allah - Dicky Syahfrizal; Aziz Israq (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Al-Quran Surah Al-Baqarah 285: this research aims to apply the values ​​of faith in the daily lives of Muslims. "The Obligation of Faith in Allah, and the Messengers, Angels, and His Book" explains the concept of i'jaz (human inability to compete with the Koran) contained in this verse. This research examines the obligation to believe as the core teachings of Islam, including faith in Allah, the messengers, angels, and His books. Through a textual analysis and interpretation approach, this journal shows how this verse emphasizes the importance of faith in a Muslim's life and its implications for morals and behavior I'jaz in Surah Al-Baqarah provides deep insight into the importance of faith in Islam and the challenge for believers to follow these teachings consistently.